ZAKAT SARANG BURUNG WALET HASIL PENANGKARAN - Santoso, Dri (P3M STAIN Jurai Siwo Metro, 2011)
Zakat is an obligation to muslim whose some wealth that enough limitation of nisab and has been possessed as long as one year (haul). Regulation of nisab and how many percentage of zakat will be taken and thenÂ wil be distributed to person whose rigt to receive (muzakky). Fuqaha has agree for several kind of property for example gold, silver, agriculture, castle ang trading Is taken it zakat. But there are some wealth have been gotten in modern job, like wealth of wallet bird nest not yet regulation, is it must be taken zakat or no? how many nisab dan how many percentage of zakat.This research has goal to knaw regulation of wallet bird nest zakat, how many nisab and how many percentage of zakat must be taken. The location of research in Metro and East Lampung. The population of this research are muslim who has building wallet bird. Sampling technique used purposive sampling. All of wealth must be taken zakat including wallet bird nest, nisab of wallet bird nest is 3 on gold dan 21/2% quota of zakat, is based on analogy (qias) with wealth of trading as same as with zakat of gold and silver.Â Keywords: wealth, zakat, nisab, haul,obligation